Unraveling the reversible redox mechanism of Li6PS5Cl solid electrolyte in all-solid-state lithium-sulfur batteries - Lee, Eunbyoul; Kim, Heejun; Choi, Hamin; Kim, Se Young; Chung, Kyung Yoon (Royal Society of Chemistry, 2024)
We reveal the reversible redox mechanism of Li6PS5Cl in composite cathodes for practical all-solid-state lithium-sulfur batteries. The limited electrochemical reactivity of the non-conducting sulfur-based active material induces the formation of Li6PS5Cl decomposition products, which allows the recrystallization of Li6PS5Cl through a reversible redox process, contributing to the composite cathode capacity.